Tren Topik Penelitian Pembelajaran Keterampilan Menulis Karya Sastra: Analisis Bibliometrik dengan Aplikasi Vosviewer - Ayu Cahyani, Putri; Awaliyah, Mia; Amanah (Indo-MathEdu Intellectuals Journal, 2025)
Research in the field of teaching literary writing skills is a topic that has been widely studied. Therefore, metadata from studies on this topic needs to be analyzed to uncover any novelty. This study employs bibliometric analysis using the VOSviewer application. It is a qualitative descriptive study. The data comprises 500 articles related to literary writing skills published between 2019 until 2024. Data collection was conducted using metadata sourced from Google Scholar, with the assistance of the Publish or Perish (POP) application. The data obtained was analyzed using VOSViewer. The analysis results are presented through Item Clustering, Network Visualization, Overlay Visualization, and Density Visualization. The study found that literary writing skills have been a frequently researched topic over the past five years. However, researchers can still identify novel areas through more specific subtopics. Some of the more recent topics in literary writing skills are related to the "Merdeka Belajar" era. In addition, the genre of short stories presents opportunities for further exploration in relation to writing skills. The findings of this study can serve as a foundation for other researchers to delve deeper into the subtopics within the field of teaching literary writing skills, particularly those that have not been extensively studied